Capronia capucina - Sanchez, Romina Magali
Capronia capucina is known from only two sites of the Andean Patagonian forest of Argentina, associated with bark of living Nothofagaceae trees. It is saprophytic on the bark of Nothofagus alpina and N. antarctica. These plants are restricted to the Argentinean and Chilean Patagonian forests, in areas with a temperate to cold climate with high humidity, strong westerly winds and frequent snowfall. It is suspected that the fungus may occur along the distribution of these known hosts plants, over 700m asl, and probably in the more humid areas. However, further surveys are required to ascertain whether this is the case or not.There are many threats to the habitat of the associated plants, such as fires (the principal threat), the use of the forest land for housing installations, livestock, extraction of wood and soil, recreation activities and tourism; and these are causing a decline in the forest area. An additional and growing threat to this habitat is climate change, which is of particular concern as Nothofagaceae trees exhibit poor dispersal ability and may not be able to adapt in response to a warming climate. Despite extensive surveys elsewhere in the Andean Patagonia forest, additional records for the species have not been made so far, making estimation of population size and trend difficult. It is not possible to accurately estimate the extinction risk of this species, and so C. capucina is assessed as Data Deficient. Fil: Sanchez, Romina Magali. Universidad Nacional del Sur. Departamento de Biología, Bioquímica y Farmacia; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Centro de Recursos Naturales Renovables de la Zona Semiárida. Universidad Nacional del Sur. Centro de Recursos Naturales Renovables de la Zona Semiárida; Argentina